Piano Sonatas [de Wolfgang Amadeus Mozart] = Klaviersonaten [de Wolfgang Amadeus Mozart] = Sonates pour piano [de Wolfgang Amadeus Mozart] = Sonate per pianoforte [de Wolfgang Amadeus Mozart] - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: Sonatas para piano KV 279/189d, KV 280/189e, KV 281/189f, KV 282/189g, KV 283/189h, KV 284/205b Dürnitz, KV 309/284b, KV 310/300d, KV 311/284c, KV 330/300h, KV 331/300i, KV 332/300k, KV 333/315c, KV 475, KV 457, KV 545, KV 570, KV 576, KV 533 and 494.